Analysis Of Trust And Quality Of Service On Customer Satisfaction Through Price As An Intervening Variable (Study On Aia Insurance Branch Of Bukopin Slamet Riadi) - Niken Paradibha; Ashary Anshar; Novita Rosanti; Natsir Muhammad (MANAGER: Journal of Management and Administration Science, 2023)
This study aims to analyze (1) does trust have a positive effect on price, (2) does service quality affect price, (3) does trust have a positive effect on customer satisfaction, (4) does service quality have a positive effect on customer satisfaction, ( 5) Does trust have a positive effect on customer satisfaction through price, (6) Does service quality have a positive effect on customer satisfaction through This study aims to analyze (1) does trust have a positive effect on price, (2) does service quality affect price, (3) does trust have a positive effect on customer satisfaction, (4) does service quality have a positive effect on customer satisfaction, ( 5) Does trust have a positive effect on customer satisfaction through price, (6) Does service quality have a positive effect on customer satisfaction through price, (7) Does price have a positive effect on customer satisfaction. This research was conducted at AIA Asuransi Slamet Riadi Branch from June to July 2023. The population in this study totaled 500 customers of AIA Asuransi Slamet Riadi Branch. The sample in this study is the Slovin formula. Thus the sample is 100 people from AIA Insurance, Slamet Riadi Branch. The data analysis method used in this study is the Sobel Test. The results showed that (1) Trust has a positive effect on price, (2) Service quality has an effect on price, (3) Trust has a positive effect on customer satisfaction, (4) Service quality has a positive effect on customer satisfaction, (5) Trust has a positive effect on customer satisfaction through price, (6) price mediates the effect of trust on customer satisfaction, (7) price mediates the effect of service quality on customer satisfaction